Curaca Ashaninka - Centro de Estudios Teológicos de la Amazonía (CETA) (My University, 1900)
SPANISH: Se observó a un Curaca Ashaninka vistiendo su tradicional Cushma.
ENGLISH: An Ashaninka Curaca was observed wearing his traditional Cushma.

SPANISH: Se observó a un Curaca Ashaninka vistiendo su tradicional Cushma.
ENGLISH: An Ashaninka Curaca was observed wearing his traditional Cushma.
Ashaninka Cacique
Keywords: Iquitos (Perú)|~|Native Communities|~|Perú|~|Indigenous or Native populations|~|Chiefs and Authorities.|~|Iquitos (Perú)|~|Comunidades Nativas|~|Perú|~|Poblaciones Indigenas u Originarias|~|Jefes y Autoridades.|~|Iquitos (Peru)|~|Native Communities|~|Peru|~|Indigenous or Native Populations|~|Chiefs and Authorities.